Elastic and plastic Poisson's ratios of nanoporous gold. (1st January 2016) - Lührs, Lukas; Soyarslan, Celal; Markmann, Jürgen; Bargmann, Swantje; Weissmüller, Jörg
Graphical abstract: Abstract: We explore the elastic and plastic Poisson's ratios, ν E and ν P, of nanoporous gold, using digital image correlation during compression experiments including load/unload segments. The two coefficients differ significantly, with ν E independent of the ligament size, L, and with a trend for ν P ∝ L at not too large L . Disorder in the network of ligaments may explain why ν E is smaller than predicted by lattice-based models. Finite element simulations, based on the Deshpande–Fleck constitutive law, validate the data analysis. The constitutive law captures work-hardening and transverse flow of nanoporous gold in good agreement with the experiment.